2015
DOI: 10.1111/jcpp.12379
|View full text |Cite|
|
Sign up to set email alerts
|

White matter microstructure and developmental improvement of hyperactive/impulsive symptoms in attention‐deficit/hyperactivity disorder

Abstract: Background A developmental improvement of symptoms in Attention-Deficit/Hyperactivity Disorder (ADHD) is frequently reported, but the underlying neurobiological substrate has not been identified. The aim of this study was to determine whether white matter microstructure is related to developmental improvement of ADHD symptoms. Methods A cross-sectional Magnetic Resonance Imaging (MRI) analysis was embedded in a prospective follow-up of an adolescent cohort of ADHD and control subjects (NeuroIMAGE). Mean age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 44 publications
6
64
1
Order By: Relevance
“…2i), resulting in a pooled SDM of 0.03 (95 % CI = −0.18 to 0.23, p = 0.805). Only one study [22] evaluated gestational age and birth weight and it did not find difference between the groups.…”
Section: Socio-demographic Featuresmentioning
confidence: 90%
See 2 more Smart Citations
“…2i), resulting in a pooled SDM of 0.03 (95 % CI = −0.18 to 0.23, p = 0.805). Only one study [22] evaluated gestational age and birth weight and it did not find difference between the groups.…”
Section: Socio-demographic Featuresmentioning
confidence: 90%
“…Three studies were included in the meta-analyses (Fig. 2h), resulting in a pooled SDM of 0.18 (95 % Four studies that evaluated intelligent quotient (IQ) at baseline were unanimous about not finding any influence of this factor in the persistence of ADHD [21,22,26,28]. We meta-analyzed data from three studies (Fig.…”
Section: Socio-demographic Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study adds to the previous volumetric findings of our group with ADHD being associated with global rather than local volume reductions 6 . Other neuroimaging studies based on the same sample investigated volumetric features, 24-26 structural connectivity, [27][28][29] or functional MRI. [30][31][32][33] To the best of our knowledge, CT has not previously been studied in an ADHD sample of this size.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…48,54 Several studies have also reported altered metrics in more dorsal areas of the cerebral white matter. 48,[52][53][54][55][56] There are some intriguing differences between comparisons based on diagnostic grouping (adult ADHD versus control) and symptom measures. A recent study comparing older children and young adults with ADHD and controls reported multiple clusters in which either FA or MD were lower in the ADHD group compared with controls.…”
Section: Neurobiologymentioning
confidence: 94%